Application of GPR to Detect Lost Valve Chambers in a Utility Network - Hayat, Tanzim; Kamal, A S M Maksud (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
The exact geographic location of the fresh water transmission network of Dhaka WASA was not known to the agency. With time and development works, access to many such underground valve chambers were lost. Their recovery was usually done through manual digging and trenching. This was expensive, time- and labour-consuming, often led to traffic jams, and the rate of success was low. This study was conducted to use the non-intrusive method of Ground Penetrating Radar to locate those valves as an alternative. A total of 27 out of the 41 lost nodes in the network was successfully recovered and their precise location was recorded using RTK-GNSS. The article presents the detail procedure of locating the valve chambers of underground pipeline network. It also highlights how the lack of collaboration between agencies are causing water supply and maintenance problems to this day, and how infrastructure development of one agency may erode successes of another. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 12(2), 2023, P 139-151